Perancangan Decorative Typeface Adaptasi dari Motif Gorga Dalihan Na Tolu untuk Melestarikan Seni Ornamen Batak Toba - Rendy Prayogi; Mhd. Rusdi Tanjung; Dea Aprillia Manik (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Communication is the most important activity in everyday life, language and writing are effective communication tools both verbally and visually, communication in a visual context will be conveyed through typography. As time and technology develop, typography plays an important role and presents many types and styles of letters almost every day which have their own characteristics and uniqueness, one of which is decorative typefaces which have minimalist and geometric shapes as benchmarks. The design of this decorative typeface typography aims to create letters, numbers and punctuation characters that have their own uniqueness and characteristics by exploring the potential forms in the Gorga Dalihan Na Tolu motif in the Toba Batak Traditional House